2020
DOI: 10.1111/jfbc.13546
|View full text |Cite
|
Sign up to set email alerts
|

The combination of ginger powder and zinc supplement improves the fructose‐induced metabolic syndrome in rats by modulating the hepatic expression of NF‐κB, mTORC1, PPAR‐α SREBP‐1c, and Nrf2

Abstract: Although studies have shown that ginger, as an herbal remedy and zinc are able to improve inflammation, oxidative stress, autophagy, and metabolism of lipid and glucose, their molecular mechanisms are unknown. Therefore, this study was aimed to examine the therapeutic effects of ginger with zinc supplement for eight weeks on fructose-induced metabolic syndrome (MS). Ninety-six adult male Sprague Dawley rats (220 g ± 20) were randomly assigned to twelve controlled and treated groups. After the last treatment se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 64 publications
9
24
0
Order By: Relevance
“…Moreover, zinc supplementation also leads to a higher level of TNF-α bound monocytes, which may benefit the immune response system (37). On the other hand, some fundamental experimental evidence indicates that long term zinc supplementation directly improves MetS in animal model (38), and decreases several metabolic disorder makers, lipid accumulation, and toxicity (39)(40)(41). Above all, the existing clinical and experimental data are strongly consistent with our results.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, zinc supplementation also leads to a higher level of TNF-α bound monocytes, which may benefit the immune response system (37). On the other hand, some fundamental experimental evidence indicates that long term zinc supplementation directly improves MetS in animal model (38), and decreases several metabolic disorder makers, lipid accumulation, and toxicity (39)(40)(41). Above all, the existing clinical and experimental data are strongly consistent with our results.…”
Section: Discussionsupporting
confidence: 89%
“…The phytochemical results of this study showed that ginger extract had high antioxidant activity. These results can be due to the high levels of phenolic and flavonoid compounds that have been well demonstrated by previous studies (Ahmed Mustafa et al., 2021; Akbari et al., 2017). In addition, the results of HPLC showed that 6‐gingerol, 6‐shogaol, and 8‐gingerol are the main components of ginger extract in our study.…”
Section: Discussionsupporting
confidence: 73%
“…Mean ± SD of body weight in different groups during the period of the study. Mismatched lowercase letters indicate significant differences between groups levels of phenolic and flavonoid compounds that have been well demonstrated by previous studies (AhmedMustafa et al, 2021;Akbari et al, 2017). In addition, the results of HPLC showed that 6-gingerol, 6-shogaol, and 8-gingerol are the main components of ginger extract in our study.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…The present results showed a normal histological appearance of the liver tissue after ginger administration at different intervals. Our results are consistent with those obtained by Mustafa et al (24) found that rats who received ginger (50 and 100 mg/kg/BW) orally daily for eight weeks showed a normal arrangement of hepatocytes and proper central vein as the control group. These results are supported by the work of Gad EL-Hak et al (25) observed that MSG administered orally to the pregnant female rat at a dose of 1 g/5 mL/kg body weight from day 0 to day 20 of pregnancy caused severe fatty degeneration, focal necrosis with a pyknotic nucleus, dilation of sinusoids and infiltration of inflammatory cells in the portal area with proliferation and hyperplasia of the bile duct.…”
Section: Discussionsupporting
confidence: 93%